Emotional and Cognitive Preservice Science Teachers’ Engagement While Living a Model-Based Inquiry Science Technology Engineering Mathematics Sequence About Acid-Base - López-Banet, Luisa; Aguilera, David; Jiménez-Liso, M. Rut; Perales-Palacios, F. Javier (Frontiers in Psychology, 2021)
Science inquiry and modelling activities have been proved to heighten emotional situations; therefore, research about emotions should aim to identify which activities promote student engagement with Science, Technology, Engineering and Mathematics fields through multidimensional models that include emotional and cognitive engagement. This research is focused on science teachers’ need to carefully review their classroom instructions to ensure that students are provided with opportunities to develop appropriate understandings of acid/base models (and their concepts). To achieve this, we have implemented a short model-based inquiry acid-base instructional sequence in the context of a TV-spot about chewing gum. A descriptive, non-experimental quantitative methodology with a heuristic (emotional: self-report questionnaire; and cognitive: self-regulation questionnaire) has been used to analyze what Pre-Service Secondary Education Teachers from several Spanish universities recognize to have learned and felt in each activity. Differences regarding knowledge declared by the participants were identified in all the tasks from before to after carrying them out. Furthermore, the results seem to indicate that there are significant relationships between the knowledge and the emotions, being different depending on the skill involved. Significant correlations between emotions have been found. However, there were no significant correlations with either rejection and knowledge or with other emotions, which points to emotional engagement. Generally, no significant differences were identified between emotions and gender or universities, with some exceptions between genders in two tasks. Thus, the results led us to reflect on the instructional sequence implementation’s ability to bring awareness to the learning process and how it produces multidimensional engagements.